Strategy for Optimizing Tax and Levy Revenue for the Development of Banjarmasin City - Arman Arisallo (Al-Makki Publisher, 2026)
This study evaluates the performance of Banjarmasin City's Regional Original Revenue (PAD) from taxes and levies, identifies optimization efforts, and formulates strategies to enhance tax and levy revenues for city development. A mixed-methods approach was used, combining quantitative analysis of tax and levy realization data from 2018–2022 with qualitative analysis through interviews with key informants from the BPKPAD. Results show that regional tax performance is generally effective, particularly for hotel tax, restaurant tax, street lighting, and BPHTB. However, some taxes, like the swallow's nest tax and billboard tax, show low effectiveness in certain years. Regional levies contribute minimally to PAD, with several levies no longer generating revenue. The fiscal independence ratio indicates that Banjarmasin City is still heavily dependent on central transfer funds. Optimization efforts include intensifying tax collection, digitizing payment services, and enhancing taxpayer socialization. SWOT analysis identified strategies: aggressive (SO), diversification (ST), turn-around (WO), and defensive (WT). The study recommends improving regional tax governance, increasing human resource capacity, updating tax-levy databases, and leveraging digital technology to enhance compliance and supervision.